Buklod: A prototype utilizing web & mobile technologies for community development - Ona, Sherwin E. (Animo Repository, 2010)
Many regard knowledge as the quintessential resource. Current management and governance literature suggests that knowledge if tapped and utilized can result to increased productivity through quality decision-making and responsiveness to constituent-citizen demands. Although this viewpoint is quiet true in the realm of business, little is written about the knowledge management in governance especially on the topic of community (rural) development. This paper treats the exploration of indigenous knowledge as a research frontier ripe for exploration. The Barangay-based Utilization of Knowledge for Local Development (BUKLOD) aims to create a systems prototype that aims to harness local knowledge resources supporting the community development efforts of selected communities in the municipality of Barotac-Viejo, Province of Iloilo. Through the use of web and mobile technologies, BUKLOD intends to support the ongoing community development efforts under the area specific development program (ASDP) being implemented by the local government cooperation with its NGO partner Kaisahan, Inc.